Comparative Study of Some Biomechanical Variables of Handspring Artistic performance phases (front handspring followed by a summersault and Arabian Summersault) on the Vault For Advance Artistic Gymnastics For Men - Saleh, Ayad (Journal of Physical Education, 2016)
The importance of the research lies in the motor analysis of handspring on the vault to develop the level of scores in Iraqi Artistic gymnastics for men. The problem of the research lies in the lack of interest in using biomechanical standards in using exercises to develop the biomechanical variables of this skill. The aim of the research is to identify the differences in some biomechanical values of handspring (front summersault and Arabian summersault). The subjects were Iraqi national League of artistic gymnastics for men. The aim of the research is to use videotaping and biomechanical analysis to find the results. The researchers concluded that during the landing on the vault and flight phases the biomechanical variables are the same in both skills except in vertical distance, height and first flight time.